ER stress in D1-MSNs mediates cocaine-induced behavioral plasticity via the ATF4–SPTLC1 axis - Zhao, Yue; Li, Shu; Jiang, Linhong; Zhao, Ying; Kuang, Weihong; Wei, Qingfan; Zhou, Yuanyi; Han, Shuang; Wang, Liang; Li, Hongchun; Dai, Yanping; Yang, Xiaofeng; et al. (Frontiers in Pharmacology, 2025)
BackgroundCocaine-induced endoplasmic reticulum (ER) stress has been increasingly recognized, but its neuronal specificity and functional significance remain unclear. Because the ER is also a major site for lipid and sphingolipid biosynthesis, cocaine-triggered ER stress may influence metabolic pathways linked to cellular stress signaling. Here, we sought to define the cell-type specificity and downstream consequences of cocaine-induced ER stress in the nucleus accumbens (NAc).MethodsWe combined cocaine administration with ultrastructural analysis of ER morphology, immunohistochemical and molecular profiling of ER stress pathways, and assays of sphingolipid biosynthesis in the NAc. We also evaluated the effects of pharmacological inhibition of ER stress and sphingolipid synthesis, and performed D1-MSN–specific knockdown of Atf4 and Sptlc1 to assess their contributions to cocaine-induced behavioral and neuroplastic adaptations.ResultsCocaine selectively activated ER stress in dopamine receptor 1 (D1)–expressing medium spiny neurons (MSNs), marked by induction of activating transcription factor 4 (ATF4). Cocaine also upregulated serine palmitoyltransferase long-chain base subunit 1 (SPTLC1), and promoter analysis with functional validation identified Sptlc1 as a direct target of ATF4. ATF4 activation was thus coupled to remodeling of sphingolipid metabolism. Blocking ER stress or sphingolipid synthesis–and D1-MSN–specific knockdown of Atf4 or Sptlc1—markedly reduced cocaine-induced behavioral and neuroplastic changes.DiscussionThese findings identify a D1-MSN ER stress response that promotes cocaine-induced neuroadaptations via the ATF4–SPTLC1 signaling axis and suggest a potential therapeutic target for cocaine addiction.